The complete chloroplast genome of Forsythia mira, an endemic medicinal shrub in China. Issue 1 (2nd January 2020) - Gao, Su; Bai, Ji-Qing; Liu, Mi-Li; Wang, Peng-Fei; Li, Na; Yang, Lei; Wang, Xiao-Ping; Li, Zhong-Hu
Abstract: Forsythia mira M. C. Chang (Oleaceae) is an endemic medicinal shrub in China. In this study, we first characterized its whole plastid genome sequence using the Illumina sequencing platform. The plastid genome was 156, 485 bp in length, comprising of a large single copy (LSC) region of 87, 223 bp, a small single copy (SSC) region of 17, 830 bp, and two inverted repeat regions (IRs) of 51, 432 each. The genome of F . mira contained 133 genes, including 86 protein-coding genes, 37 transfer RNAs (tRNA), and 8 ribosomal RNAs (rRNA). The phylogenetic analysis showed that F . mira was placed as a sister to the congeneric F . suspensa .